Bacterial co-infections and antibiotic resistance in patients with COVID-19 - Mahmoudi, Hassan (German Medical Science GMS Publishing House, 2020)
Background: Bacterial co-infections are frequently identified in viral respiratory infections and are significant reasons for morbidity and mortality. Information on the prevalence of bacterial co-infection in patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is lacking. The purpose of this study was to determine the prevalence of bacterial infections and antibiotic resistance in patients with coronavirus disease (COVID-19).Methods: In a cross-sectional study, blood culture (BC) and endotracheal aspirate (ETA) were obtained from COVID-19 patients (RT-PCR positive for SARS-CoV-2). The bacterial isolates were confirmed by the standard microbiological methods. Antibiotic resistance was determined using the disk diffusion method.Results: Among these 340 patients with COVID-19, a total of 43 (12.46%) patients had secondary bacterial infections. The most common bacteria isolated through ETA and BC included Klebsiella species 11 (25.59%), methicillin-sensitive (MSSA) 9 (20.93%), 7 (16.28%), methicillin-resistant (MRSA) 6 (13.95%), 5 (11.63%), 1 (2.32%), and 4 (9.30%). The results showed that Enterobacteriaceae isolates from COVID-19 patients had the highest resistance to cotrimoxazole (74%), piperacillin (67.5%), ceftazidime (47.5%), and cefepime (42.5%). All isolates were susceptible to amikacin (100%). isolates were susceptible to vancomycin (100%) and the rates of resistance to oxacillin, erythromycin and clindamycin were over (90%). was susceptible (90%) to imipenem.Conclusions: Bacterial co-infection is relatively infrequent in hospitalized COVID-19 patients. According to the results, one of the causes of death of these patients could be a secondary infections.